2019
DOI: 10.1002/net.21890
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization of dynamic route planning in same‐day delivery networks with one‐time observation of new demand

Abstract: Local delivery networks expect drivers to make deliveries to and/or pickups from customers using the shortest routes in order to minimize costs, delivery time, and environmental impact. However, in real-world applications, it is often the case that not all customers are known when planning the initial delivery route. Instead, additional customers become known while the driver is making deliveries or pickups. Before serving the new demand requests, the vehicle will return to the depot for restocking. In other w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…The researchers concluded that their best policy minimized the average cost of an a priori policy by 9.1% and maximized the orders delivered. A real problem that exists for companies attempting to break into the SDD category is the ability to evolve as an e-commerce platform without compromising revenue (Ulmer, 2017;Kawa et al, 2018;Scherr et al, 2018;Yao et al, 2019). Lin et al (2018) evaluated the efficiency of on-demand same-day delivery models with regards to fuel cost, transportation time, and emission cost.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers concluded that their best policy minimized the average cost of an a priori policy by 9.1% and maximized the orders delivered. A real problem that exists for companies attempting to break into the SDD category is the ability to evolve as an e-commerce platform without compromising revenue (Ulmer, 2017;Kawa et al, 2018;Scherr et al, 2018;Yao et al, 2019). Lin et al (2018) evaluated the efficiency of on-demand same-day delivery models with regards to fuel cost, transportation time, and emission cost.…”
Section: Literature Reviewmentioning
confidence: 99%
“…En [79] proponen un SVRP no capacitado con tiempos de viaje inciertos a lo largo de los arcos para determinar la ruta en ventanas de tiempo estipuladas, para lo cual incluyen un nuevo criterio de decisión que penaliza el nivel de servicio. Por su parte [87], consideran un problema SDD de una red de distribución local con un solo vehículo, existe incertidumbre en la ubicación de los clientes, ya que estos van apareciendo mientras el vehículo cubre otra ruta, por esto se hace necesario que el vehículo vuelva al depósito para aprovisionarse antes de servir a los nuevos clientes, además considera los costos asimétricos y su objetivo es minimizar el tiempo e impacto ambiental.…”
Section: Capacidad En Los Vehículosunclassified
“…České firmy ve svých propagačních materiálech běžně uvádí, že instalací sledovacího zařízení může provozovatel ušetřit až 20 % nákladů na palivo. (Zhang et al, 2019;Yao et al, 2019).…”
Section: Současný Stav Problematiky V čEské Republiceunclassified